Correlation of Triglyceride/HDL-Cholesterol Ratio and Visceral Adiposity Index with 25(OH)D in Obese Female - Monica Monica; Meita Hendrianingtyas (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Obesity is a condition of excess body fat mass with cardiometabolic complications. The levels of serum 25-hydroxyvitamin D (25(OH)D) decrease in obesity because it is stored in adipose tissue compartments and is related to dyslipidemia conditions. A high triglyceride/HDL-cholesterol (TG/HDL-C) ratio in obesity is related to dyslipidemia. Visceral Adiposity Index (VAI) is one of the parameters indicating central obesity related to visceral fat distribution in dyslipidemia conditions. This study aimed to prove a correlation between TG/HDL-C ratio and VAI with 25(OH)D levels in obese females. Observational study with cross-sectional design in 66 female patients. HDL-C examinations and triglyceride using the enzymatic colorimetry method. The TG/HDL-C ratio was calculated by dividing TG by HDL. The equation obtained visceral adiposity index (WC/(36.58+(1.89xBMI)) x (TG/0.81) x (1.52/HDL). 25(OH)D examinations used the Enzyme Linked Fluorescent Immunoassay (ELFA) method. Relationship status used the spearman rank test (p<0.05). Median 25(OH) levels were 9.75 (8-18.6)ng/mL. There was a weak negative correlation between TG/HDL-C ratio with 25(OH)D levels in obese females (p=0.020; r= -0.287) and VAI with 25(OH)D in obese females (p=0.019; r= 0.287). There was a weak negative correlation between TG/HDL ratio and VAI with 25(OH)D in obese female patients.